2018
DOI: 10.1038/s41467-018-02926-5
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptomic atlas of aged human microglia

Abstract: With a rapidly aging global human population, finding a cure for late onset neurodegenerative diseases has become an urgent enterprise. However, these efforts are hindered by the lack of understanding of what constitutes the phenotype of aged human microglia—the cell type that has been strongly implicated by genetic studies in the pathogenesis of age-related neurodegenerative disease. Here, we establish the set of genes that is preferentially expressed by microglia in the aged human brain. This HuMi_Aged gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
447
4
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 400 publications
(481 citation statements)
references
References 32 publications
26
447
4
4
Order By: Relevance
“…Recent transcriptomic studies, the majority of which have been conducted in mice, have greatly advanced our knowledge of the functional profile of microglia (Butovsky et al, ; Darmanis et al, ; Galatro et al, ; Hickman et al, ; Zeisel et al, ), their regional heterogeneity in the CNS (Grabert et al, ; McCarthy, ), and altered functional profile associated with neurodegeneration (Holtman et al, ; Keren‐Shaul et al, ; Miller et al, ; Vincenti et al, ). However, key differences between mouse and human microglia have been suggested (Galatro et al, ; Olah et al, ), emphasizing the importance of better characterizing the functional profile of human microglia in health and disease. Our initial investigations demonstrated that published microglia gene signatures vary considerably in their size and composition relative to one another.…”
Section: Discussionmentioning
confidence: 99%
“…Recent transcriptomic studies, the majority of which have been conducted in mice, have greatly advanced our knowledge of the functional profile of microglia (Butovsky et al, ; Darmanis et al, ; Galatro et al, ; Hickman et al, ; Zeisel et al, ), their regional heterogeneity in the CNS (Grabert et al, ; McCarthy, ), and altered functional profile associated with neurodegeneration (Holtman et al, ; Keren‐Shaul et al, ; Miller et al, ; Vincenti et al, ). However, key differences between mouse and human microglia have been suggested (Galatro et al, ; Olah et al, ), emphasizing the importance of better characterizing the functional profile of human microglia in health and disease. Our initial investigations demonstrated that published microglia gene signatures vary considerably in their size and composition relative to one another.…”
Section: Discussionmentioning
confidence: 99%
“…This shared functionality included microglia as the main cell type, extracellular matrix as the main cellular component, and immune response as the main biological process. Microglia, constituting 5%-12% of all cells in the mouse and human brain (Lawson et al 1990;Lyck et al 2009;Olah et al 2018) and primarily known for their role in immune response, have recently been implicated in multiple brain functions including the regulation of learning-related synapse formation, synaptic plasticity, and cognition (Parkhurst et al 2013;Hong et al 2016;Tay et al 2017) and are linked with neurodegenerative and psychiatric disorders (Wolf et al 2017). Furthermore, microglial cells were shown to have different transcriptional identities in different brain regions (Grabert et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The genomic signature of aged microglia has been of great interest since the advent of next generation sequencing technologies. Unfortunately attempts to characterise them have yielded varied and often conflicting results with no clear and consistent specific genetic or protein markers for aged microglia emerging (Crotti and Ransohoff ; Wes et al ; Spittau ; Olah et al ). The aged microglia in the mouse retina exhibited significant changes in genes controlling inflammation including the NF‐κB signalling pathway and up‐regulated complement genes C3 and complement factor B (Ma et al ).…”
Section: Dystrophic and Senescent Microgliamentioning
confidence: 99%